Effect of the Environmentally Friendly Composite Materials on Physical and Thermal Properties of the Natural Composite - Syafrul Hadi; Mastariyanto Perdana (LP2M - Institut Teknologi Padang, 2018)
One of the most widely used and applied technics materials today is a composite material based on nature. Natural composites are lightweight and relatively strong and environmentally friendly, so composites based on synthetic fibers are reduced in use. This study uses constituent materials derived from shells and bunches of palm oil plant crops that function as reinforcement. Shells and fibers from empty bunch of oil palm plants are made in the form of powder. Matrix used in this research was polyester resin and epoxy resin. The volume fraction between the reinforcement and the matrix is 50:50. The fabrication process of this environmentally friendly composite is compression molding with a pressure load of 30 kg/cm2. This study aims to determine the effect of the type of composite materials on physical and thermal properties of the natural composite. The results show that natural composites are high density composites. The highest density of palm shell/polyester composite is 1,223 g/cm3 and the lowest density of oil palm empty bunch/epoxy composite is 1,021 g/cm3. The highest thermal conductivity of oil palm shell/polyester composite is 0,28 W/m.K. Thermal conductivity composite value is more influenced by binder/matrix of composites.